Determination of proximate and mineral content of selected commercial rice in Malaysia - Husain, Ariani (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
The study was conducted to determine and compare the contents of macronutrients and minerals in three types of selected commercial cooked white rice in Malaysia. The selected white rice for this study were long, medium and short white rice. The white rice was cooked according to the proper measurement of water to rice before it was dried and analysed. The macronutrients were determined by using proximate analysis (AOAC) method, total carbohydrate was determined by Anthrone method, calorie contents was determined by Bomb-Calorimetry and mineral contents were determined using Atomic Adsorption Spectrophotometer (AAS). The proximate analysis showed all samples contained 64.13 - 70.27 % of total moisture, 0.22 - 0.38 % of total ash, 0.09 - 0.46 % of crude fat, 11.11 - 26.61 % of crude protein, and 6.53 -24.22% of total carbohydrates. The calorie content were 3.753-3.999 kcaVg in all of the samples. Based on the mineral analysis, potassium was the most abundant mineral (0.41 - I .03 mg/L) whereas magnesium content (0.11 - 0.18 mg/L) was the lowest mineral in all cooked white rice samples. Sodium and calcium contents in the samples were (0.41 - 0.70 mg/L) and (0.19- 0.54 mg/L) respectively. The result shows that the mineral contents were significant different (p < 0.05) between all of the samples. The overall results showed that the long white rice has the lowest content of moisture, ashing, protein and calorie compare to other samples. The medium white rice has the lowest fat and carbohydrate content. Magnesium and sodium content were the highest in the long white rice, while calcium content was the highest in the short white rice and potassium content was highest in the medium white rice.